Why are professors liberal? - Gross, Neil; Fosse, Ethan (Theory and society, 2012)
The political liberalism of professors—an important occupational group and anomaly according to traditional theories of class politics—has long puzzled sociologists. This article sheds new light on the subject by employing a two-step analytic procedure. In the first step, we assess the explanatory power of the main hypotheses proposed over the last half century to account for professors' liberal views. To do so, we examine hypothesized predictors of the political gap between professors and other Americans using General Social Survey data pooled from 1974—2008. Results indicate that professors are more liberal than other Americans because a higher proportion possess advanced educational credentials, exhibit a disparity between their levels of education and income, identify as Jewish, non-religious, or non-theologically conservative Protestant, and express greater tolerance for controversial ideas. In the second step of our article, we develop a new theory of professors' politics on the basis of these findings (though not directly testable with our data) that we think holds more explanatory promise than existing approaches and that sets an agenda for future research.